1978
DOI: 10.2115/fiber.34.6_t259
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Wool With Potassium Cyanide

Abstract: The reaction of Merino wool fibers with aqueous KCN was studied. The cystine (CYS) and lanthionine (LAN) contents in the hydrolysates of wool samples were determined by the gas chro matographic method. The CYS content decreased and the LAN content increased with the treating time. The sum of CYS and LAN contents, that is, the total crosslink content, decreased to a minimum and returned to the original value as the reaction progressed. In order to see the effect of organic solvents on the reaction of wool wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
1993
1993

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Kajiyama et al 4 investigated crosslinking structure of wools treated with potassium cyanide, and the number of crosslinks was evaluated by measuring the degree of swelling in formic acid according to the method of Caldwell and Milligan.g They reported that a part of intermolecular disulfide crosslinks converts to intramolecular monosulfide crosslinks.…”
Section: Introductionmentioning
confidence: 99%
“…Kajiyama et al 4 investigated crosslinking structure of wools treated with potassium cyanide, and the number of crosslinks was evaluated by measuring the degree of swelling in formic acid according to the method of Caldwell and Milligan.g They reported that a part of intermolecular disulfide crosslinks converts to intramolecular monosulfide crosslinks.…”
Section: Introductionmentioning
confidence: 99%